2020
DOI: 10.1002/ar.24547
|View full text |Cite
|
Sign up to set email alerts
|

Cellular and molecular mechanisms in the development of a cleft lip and/or cleft palate; insights from zebrafish (Danio rerio)

Abstract: Human cleft lip and/or palate (CLP) are immediately recognizable congenital abnormalities of the face. Lip and palate develop from facial primordia through the coordinated activities of ectodermal epithelium and neural crest cells (NCCs) derived from ectomesenchyme tissue. Subtle changes in the regulatory mechanisms of NCC or ectodermal epithelial cells can result in CLP. Genetic and environmental contributions or a combination of both play a significant role in the progression of CLP. Model organisms provide … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 85 publications
0
6
0
Order By: Relevance
“…During palate development, the frontonasal mesenchyme process and the mesenchyme of the maxillary processes are derived from migratory neural crest cells. Previous research has suggested that the human primary palate is homologous to the medial ethmoid region and the secondary palate is homologous to the lateral ethmoid region of zebrafish [41,42]. The V-shaped fusion seam of the frontonasal process and the bilateral maxillary processes of the human palate are analogous to the V-shaped junction found in the zebrafish ethmoid cartilage.…”
Section: Introductionmentioning
confidence: 85%
“…During palate development, the frontonasal mesenchyme process and the mesenchyme of the maxillary processes are derived from migratory neural crest cells. Previous research has suggested that the human primary palate is homologous to the medial ethmoid region and the secondary palate is homologous to the lateral ethmoid region of zebrafish [41,42]. The V-shaped fusion seam of the frontonasal process and the bilateral maxillary processes of the human palate are analogous to the V-shaped junction found in the zebrafish ethmoid cartilage.…”
Section: Introductionmentioning
confidence: 85%
“…In this case, the microvilli of RPE cells interact with photoreceptor outer segments of the neural retina ( 20 ). Another example is the fusion of three prominences of the facial epidermis during the formation of the lips, mouth, and palate, in which a disturbed process results in a cleft of the lip or the palate ( 21 ) ( 22 ) ( 23 ). However, there are currently no reports of similar structures observed in these tissues.…”
Section: Discussionmentioning
confidence: 99%
“…Impaired formation of the ethmoid plate in zebrafish is considered to be homologous to cleft palate in mammals. 6,[37][38][39][40][41] However, ethmoid plate formation in zebrafish occurs by convergence of frontonasal and maxillary neural crest cells, which is analogous to the mammalian hard palate. 41 As a result, the soft palate that forms approximately one-third of the roof of the mammalian mouth 42 is absent in zebrafish.…”
Section: Discussionmentioning
confidence: 99%